The Role of Local Customs and Traditions in Maintaining Social Stability: A Case Study of Nubian Weddings in Egypt - Wicaksono, Imam; alGayyar, Sherif Sa’ad; Hassan, Ahmed Hassan Mohammad (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2024)
This study intends to evaluate how the wedding traditions of the Nubian community in Egypt preserve cultural identity and sustain social stability in the face of globalization pressures. These traditions encompass rites such as restrictions against marrying non-Nubians, engagement ceremonies, and henna applications, expressing the collective ideals of the community. This study uses a library research method to examine pertinent material using four important functions—adaptation, goal accomplishment, integration, and pattern maintenance—are assessed in the study using Talcott Parsons' AGIL theory. Thematic data from sociological and ethnographic sources pertaining to Nubian cultural activities were analyzed using a literature review methodology. The findings show that the role of adaptation is represented by the prohibition on marriage with non-Nubians, which tries to preserve the integrity of cultural identity. Customary agreements during engagement ceremonies, which improve interfamily connections, demonstrate goal accomplishment. Collective rituals that strengthen community cohesion, like group prayers, are one way that integration is demonstrated. Pattern maintenance is accomplished by symbolic parts of rituals, such as the application of henna, which ensures that traditional values are passed down through generations. These results support the idea that wedding customs serve as a means of maintaining social harmony and cultural continuity in the globalization era